2017
DOI: 10.1007/s40544-017-0180-8
|View full text |Cite
|
Sign up to set email alerts
|

Oil-soluble ionic liquids as antiwear and extreme pressure additives in poly-α-olefin for steel/steel contacts

Abstract: Abstract:To enhance the lubricating and extreme pressure (EP) performance of base oils, two types of oil-soluble ionic liquids (ILs) with similar anion albeit dissimilar cations were synthesized. The physical properties of the prepared ILs were measured. The anticorrosion properties of ILs were assessed by conducting corrosion tests on steel discs and copper strips, which revealed the remarkable anticorrosion properties of the ILs in comparison with those of the commercial additive zinc dialkyldithiophosphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 42 publications
(37 reference statements)
1
32
0
Order By: Relevance
“…The most popular organic additives in recent years are ionic liquids and hydrogels. Ionic liquids are commonly used as industrial lubricants or lubricant additives [89,164,165]. While hydrogels have good biocompatibility and thus they are commonly used for bio-lubrication.…”
Section: Organic Additivementioning
confidence: 99%
“…The most popular organic additives in recent years are ionic liquids and hydrogels. Ionic liquids are commonly used as industrial lubricants or lubricant additives [89,164,165]. While hydrogels have good biocompatibility and thus they are commonly used for bio-lubrication.…”
Section: Organic Additivementioning
confidence: 99%
“…The results showed that oil‐miscible ILs offer superior anti‐wear performance especially at elevated temperature when both had comparable concentrations . The reduction of wear is as a result of the chemical reaction between IL or ZDDP and the interacting surfaces, which lead to form a tribofilm . However, the reason behind the superior anti‐wear performance of soluble IL than ZDDP at elevated temperature is still vague.…”
Section: Introductionmentioning
confidence: 99%
“…This study aims to synthesise benzotriazole‐bearing imidazolium‐based ILs, which can be used as additive to improve AW/EP, antiabrasive, antioxidative, and anticorrosive properties of the lubricant . The ILs were used in turbine oil formulations, and a thorough investigation has been made on the tribological properties of the lubricants ,and their performance levels are compared with turbine oils containing commercially available additive IRGALUBE 2030A.…”
Section: Introductionmentioning
confidence: 99%
“…8 A remarkable reduction in friction and wear has been observed after the addition of ILs in oil-or water-based media and in grease, suggesting that ILs are promising candidate materials as neat lubricants as well as lubricant additives. 16 This study aims to synthesise benzotriazole-bearing imidazolium-based ILs, which can be used as additive to improve AW/EP, 17 antiabrasive, antioxidative, and anticorrosive properties of the lubricant. 18 The ILs were used in turbine oil formulations, and a thorough investigation has been made on the tribological properties of the lubricants ,and their performance levels are compared with turbine oils containing commercially available additive IRGALUBE 2030A.…”
Section: Introductionmentioning
confidence: 99%